Human rights training for private security agents in Peru: characteristics, areas for improvement and their relationship with human rights - Barnaby, Bruce (2022)
This diagnosis is an exploratory study that collects information on the situation of human rights training of private security personnel in Peru, emphasizing on the evaluation of the proposed study plan certified and organized by the Peruvian State, specifically, by the supervisory entity on private security, SUCAMEC. This document seeks to present the findings on training programs and their challenges, as well as the differentiated impact on access, management and development of the policy adopted by SUCAMEC. Likewise, some questions and suggestions are raised in connection to these findings.